DEVELOPING AN EFFECTIVE ENGLISH-USE SYSTEM UNDER THE BIWEEKLY LANGUAGE POLICY IN ISLAMIC BOARDING SCHOOLS - Syafii, Muhammad Lukman; Muskitikawati, Diyah Atiek (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2026)
This community service program addressed the inconsistent use of English in an Islamic boarding school, implementing a biweekly language policy that alternates between English and Arabic. Despite formal regulations, students frequently reverted to Indonesian or local languages in daily interaction due to low confidence, limited vocabulary, and uneven monitoring. To respond to these challenges, the program developed an English-use system that integrates structured speaking routines, dormitory-based reinforcement, student language ambassadors, and mentor-supported feedback. The method consisted of four phases: needs analysis and baseline mapping, system design and material preparation, implementation during an English week cycle with shared role distribution, and monitoring and evaluation using observation logs, participation checklists, and reflective discussions. Results indicated improved English-speaking participation across dormitory and public areas, stronger implementation consistency through distributed monitoring, and more positive student engagement supported by reinforcement strategies rather than punitive control. The program demonstrates that effective language policy enactment in Pesantren requires coordinated community involvement, practical routines, and sustained supervision. Although the implementation period was limited, the initiative provides a workable model for strengthening English communication culture in multilingual boarding environments. Future programs should evaluate long-term continuity across alternating cycles and expand authentic speaking opportunities.